HUMANISTIC EDUCATIONAL VALUES IN SOEDJATMOKO’S THOUGHTS AND THEIR IMPLICATION FOR ISLAMIC HIGHER EDUCATION - Nisa , Khairun (Indonesian Journal of Interdisciplinary Islamic Studies (IJIIS), 2019)
Soedjatmoko was one of the prominent Indonesian intellectuals who offered important ideas concerning humanism, freedom, and human welfare in facing the future of Indonesian society. This research aims to (1) study the humanistic education values in the thoughts of Soedjatmoko and (2) analyze the implication of his humanistic educational thoughts on the development of Islamic higher education. This is a library research using the historical- philosophical approach. The data were collected through the documentation method and then analyzed using the content analysis technique. The result of the research showed that humanistic education values in the thoughts of Soedjatmoko include freedom, religiosity, creativity, independence, and self-actualization. The implication of the humanistic educational thought of Soedjatmoko on the development of Islamic higher education includes the urgency of reorienting Islamic higher education by concerning more with its essence, foundation, vision and mission, orientation, goal, materials, curriculum, method, teachers, students, and evaluation.